MUSCLE EFFICIENCY OF PATIENTS WEARING DIFFERENT TYPES OF MANDIBULAR IMPLANT-SUPPORTED OVERDENTURES AND CONVENTIONAL: COMPLETE DENTURES (AN IN-VIVO STUDY) - Kaify Wali Ahmed, Rizgar Mohammed Ameen Hasan (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2024)
Background and objectives: Conventional complete denture (CCD) has been used for many years, and in spite of the benefits it offers, it possesses many drawbacks. In recent years, implant-supported overdentures (ISOD) have been introduced into the dentistry field with various benefits compared to conventional complete dentures. The aim of the current study was to assess the impact of ISOD and CCD on muscle efficiency with soft and hard foods. Methods: Forty patients (25 males and 15 females) were recruited. The volunteers had a completely edentulous maxilla and mandible. They were divided into five groups, as follows: 8 patients were divided for conventional complete dentures: 8 patients with two-pieces implant ball and socket overdenture; 8 patients with two-pieces implant locator overdenture; 8 patients with a single-piece implant ball and socket overdenture; and 8 patients with an innovative implant overdenture by locator system. The construction of the lower (CCD and ISOD) and upper complete dentures was carried out. Then, the electromyography was practiced to assess muscle efficiency by testing hard foods (carrot) and soft foods (banana) in four consecutive visits. Results: The muscle efficiency test revealed significant differences between the four visits. These tests demonstrated a significant difference across the five types, although they are almost identical. However, it is evident that there are enhancements in muscle efficiency in ISODs, especially in the temporalis and masseter muscles. Conclusions: The study findings indicate that the use of implant-supported over-dentures with the locator attachment system resulted in improved muscle efficiency while consuming hard food such as carrots, particularly during the third and fourth visits. These dentures offered superior stability compared to conventional complete dentures (CCD).